Bridges and walls: Coping and emotional experiences of Arab-Bedouin female students in Israeli academia post-October 7th - Al-Said, Haled; Jaber, Saleem Abu (Journal of International Students, 2025)
Higher education is a crucial pathway for socio-economic mobility, particularly for minorities. The events of October 7th in Israel and the subsequent war in Gaza (referred to as "Swords of Iron" in Israeli terminology and "Al-Aqsa Flood" in the Palestinian narrative) exacerbated tensions between the Arab minority and the Jewish majority in Israel, impacting daily interactions in workplaces and academic campuses. This study, grounded in Antonovsky’s (1987) salutogenic model and employing a qualitative-constructivist approach (Creswell & Poth, 2018), examines the emotional responses, coping resources, and learning processes of Bedouin Arab female students during a period of heightened security tensions. For this study, 28 third- and fourth-year students from three academic institutions were interviewed. Semi-structured interviews were conducted to investigate the personal, familial, and organizational resources that supported them during this challenging time. Analysis of the interviews identified three central themes that aligned with the salutogenic model: comprehensibility, manageability, and meaningfulness.